Implementation of Virtual Routers for Network Simulation Purposes in Simulated Internet - Firmansyah, Firmansyah; Pratama, Yusuf Hendra; Purnomo, Hendri (Universitas Islam Al-Azhar Mataram, 2023)
This research aims to implement a virtual router as a network simulation solution in an artificial internet environment. Artificial internets have become important in developing and testing applications and network protocols without the need for expensive physical infrastructure. In this study, researchers used virtual router software to create a network environment that can be customized according to user needs. Researchers evaluated the performance of virtual routers in simulating various network scenarios, including reliability, scalability, and security testing. The methods used include installing and configuring virtual routers, as well as using network simulation tools to build complex topologies. Researchers also carried out performance measurements to evaluate the latency, throughput and stability of the virtual router. The research results show that the virtual router is able to simulate the network environment well, providing complete flexibility and control to the user. Although there are some limitations, such as high resource consumption in some configurations, the advantages in terms of efficiency and ease of use make virtual routers an attractive option for network simulation on artificial internet. This research is expected to contribute to the development of more effective and efficient network simulation environments, as well as assist researchers and developers in testing and developing network technology without having to rely on expensive physical infrastructure